Epistemological implications of astroglia scientific research - Pereira, Alfredo (Frontiers in Cellular Neuroscience, 2025)
Neuroglia, comprising three cell types (astrocytes, oligodendrocytes and microglia), interact with neurons and extracellular components in brain physiology. Astroglia, having as main function the control of homeostasis, modulate dynamic processes in the nervous system, including mental functions; they are crucially involved in all neurological, psychiatric and degenerative disorders and diseases. How to change the century-old neuron-centered paradigm used to explain experimental phenomena in the clinical domain? This is the question addressed in this paper. I review a new explanatory paradigm based on an “endogenous feedback” between astroglial and neuronal networks: neuronal bioelectricity generates Local Field Potentials, which are synchronized, generating a dynamic field that impacts on a multi-ion population, releasing ‘shuttles’ that induce amplitude-modulated spatiotemporal patterns on astroglial ‘calcium waves’. The ‘calcium wave’ activates other signaling processes, as the release of ions in the “synaptic cradle,” to control the temporal dynamics of spike trains of the post-synaptic neuron and metabolic processes determining behavioral and endocrine responses. The “endogenous feedback” theoretical hypothesis can be tested by means of a combination of new techniques of visualization and analysis of amplitude-modulated spatiotemporal patterns present in astroglia in vivo, registers of behavioral patterns and subjective reports (in the case of alert persons under invasive brain surgery procedures), addressing the issue of how astroglial ‘calcium waves’ modulate neuronal dynamics, mediating brain processing of stimuli to produce adaptive responses.